MAPS, ART, POWER - Wood, Denis (Espaço e Cultura, 2015)
This history of maps is a history of shifting power relations, essentially between the growing, consolidating state and its citizens, allies and enemies; but ultimately between governments and those affected by them at every level and in all aspects of life. In the process, the idea of making and using maps gradually became ways of mediating all kinds of relations among people in every walk of life. Today maps spread the power of the state into every dimension of our existence, but also show us the route to the theater, the location of animal species, and where people are having sex. At the same time, but in a comparatively minor key, maps became tools for imagining alternative worlds, mostly at the hands of novelists, but in the twentieth century maps emerged in the practices of artists. During the last century and explosively at its end and in this century, map art has become, first an eccentric gesture in this or that artist’s practice, then a marginal genre, and now a taken-for-granted form seen everywhere. Map art springs from many sources, but fundamentally it opposes itself to the contemporary form of the state whenever that might have been, to the exercise of state power, and to the status quo more generally. This follows from the fact that the map has become an indispensible part of state authority – and vice versa – so that an assault on the facticity of the map amounts to an assault on the authority of the state. In a sense this makes map art a kind of counter-mapping, though most counter-mapping is opposed merely to this or that aspect of state maps, trying to replace them. In general map art is more broadly opposed to the entire map project.